ITIL para la mejora de la gestión de problemas del área Multi Vendor Services – IBM Perú 2017 - Rengifo Bazan, Odar Renzo (2017)
The present study details the evaluation, analysis and improvement of problem management by applying the ITIL methodology, specifically to the problematic of the problem management processes of the Multi Vendor Services area in IBM Peru and the proposal to improve the current management, the which presents difficulties with the excessive times of solution of problems and increase of operating costs. To carry out the improvement, a sample of 52 records of tickets from a population of 185 corresponding to 120 days was obtained, under which the tests were carried out. The type of study used is of the experimental - applied type and the design is of a pre - experimental type since it is going to perform a test before and test after the improvement. The results were obtained; for the first indicator, the average problem solution time before the improvement was 18.5 hours and after the improvement to 6.8 hours, which means a difference of 11.7 hours equivalent to a reduction of 63.33%. For the second indicator, the average cost per problem ticket process before the improvement was 2491.97 and then the improvement to 1022.16, which means a difference of 1469.81 equivalent to a reduction of 59.0%. Finally, it was concluded that the improvement made by application of the ITIL methodology had a positive effect on the problem management process of the Multi Vendor Services area of IBM Peru.